2022
DOI: 10.1097/shk.0000000000001979
|View full text |Cite
|
Sign up to set email alerts
|

Postinjury Fecal Microbiome Transplant Decreases Lesion Size and Neuroinflammation in Traumatic Brain Injury

Abstract: Background: Traumatic brain injury (TBI) is an underrecognized public health threat. The constitutive activation of microglia after TBI has been linked to long-term neurocognitive deficits and the progression of neurodegenerative disease. Evolving evidence indicates a critical role for the gut-brain axis in this process. Specifically, TBI has been shown to induce the depletion of commensal gut bacteria. The resulting gut dysbiosis is associated with neuroinflammation and disease. Hypothesis: We hypothesized th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…111 FMT in mice also reduced post-TBI inflammatory gene expression and T-cell infiltration into the brain, possibly by regulating the inflammatory signaling between the gut and brain. 111…”
Section: Probiotics and Fecal Microbiota Transplantationmentioning
confidence: 88%
See 1 more Smart Citation
“…111 FMT in mice also reduced post-TBI inflammatory gene expression and T-cell infiltration into the brain, possibly by regulating the inflammatory signaling between the gut and brain. 111…”
Section: Probiotics and Fecal Microbiota Transplantationmentioning
confidence: 88%
“…110 In mice subjected to CCI injury, an FMT regimen that started 2 h after TBI and continued once weekly for 4 weeks resulted in a reduction in ventriculomegaly and lesion volume and preserved the white matter connectivity. 111 FMT in mice also reduced post-TBI inflammatory gene expression and T-cell infiltration into the brain, possibly by regulating the inflammatory signaling between the gut and brain. 111…”
Section: Probiotics and Fecal Microbiota Transplantationmentioning
confidence: 88%
“…In the intestinal mucosa, activation (phosphorylation) of Stat3 serves as a master regulator of Th17 cell development by upregulating the production of IL-6, IL-17A, IL-22, and RAR-related orphan receptor gamma (RORγt) ( 125 ). FMT treatment reduces the activation of microglial cells and inflammatory gene expression in a mouse model of traumatic brain injury (TBI) ( 126 ). Another study found that FMT reduced the proliferative capacity of colonic mucosal T cells in colitic mice compared with animals who did not receive FMT.…”
Section: Fecal Microbiota Transplantationmentioning
confidence: 99%
“…In addition, they found improved neurologic functional testing compared to untreated mice [ 99 ]. This same group studied the effects of daily fecal transplantation for four weeks in mice subjected to TBI and found that this resulted in reduced microglial inflammatory gene expression and even mitigated T-cell response postinjury compared to mice who were subject to TBI alone [ 100 ]. Du et al studied TBI in male rats and performed daily fecal transplantation for seven days, showing increased alpha-diversity, shifts in beta-diversity, and microbial composition differences along with improved neurological testing results and serum metabolite differences compared to rats who were subject to TBI alone after eight days [ 101 ].…”
Section: Therapeuticsmentioning
confidence: 99%